2018
DOI: 10.1002/cncr.31841
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of human papillomavirus in oropharyngeal cancer is increasing regardless of sex or race, and the influence of sex and race on survival is modified by human papillomavirus tumor status

Abstract: BACKGROUND:The purpose of this study was to evaluate the influence of sex and race/ethnicity upon prevalence trends of human papillomavirus (HPV) in oropharyngeal cancer (OPC) and survival after OPC. METHOD: This was a cohort study of patients included in the United States National Cancer Database who had been diagnosed with OPC between 2010 and 2015. Outcomes were HPV status of tumor specimens and overall survival. Sex-and race-stratified trends in HPV prevalence were estimated using generalized linear modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
3
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 40 publications
4
71
3
5
Order By: Relevance
“…4 Moreover, the design of this study pertaining to patient selection limits the generalizability of our findings specifically to surgically treated disease, which represents the treatment of 40% of patients with HPV-OPC. 55 Whether TIL density can reliably stratify risk based on biopsy specimens, as would be required for patients who plan to undergo primary radiotherapy, is unknown and represents a direction of future investigation. These results support the continued investigation of TIL density to stratify prognosis of HPV-OPC.…”
Section: Discussionmentioning
confidence: 99%
“…4 Moreover, the design of this study pertaining to patient selection limits the generalizability of our findings specifically to surgically treated disease, which represents the treatment of 40% of patients with HPV-OPC. 55 Whether TIL density can reliably stratify risk based on biopsy specimens, as would be required for patients who plan to undergo primary radiotherapy, is unknown and represents a direction of future investigation. These results support the continued investigation of TIL density to stratify prognosis of HPV-OPC.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapolation of recent national trends suggest that, in the coming years, older Caucasian men will make up the majority of new cases, whereas rates may plateau in younger Caucasian men [10,12]. Recent studies have also shown rates of HPV-positive OPSCC to be increasing in women as well as non-Caucasian individuals, demonstrating the widespread impact of HPV-positive OSPCC across all populations [13,14].…”
Section: Epidemiology Prevention and Surveillancementioning
confidence: 99%
“…Oropharyngeal carcinoma (OPC) is now the most common type of head and neck squamous cell carcinoma (HNSCC), and HPV is the primary cause of OPC in the United States . Furthermore, whereas human papillomavirus‐related oropharyngeal cancer (HPV‐OPC) was historically considered a disease of younger (age < 60 years) white men, recent studies show that HPV‐OPC is increasingly affecting broader demographics, including women, minorities, and older patients . These findings highlight the continually expanding societal impact of HPV‐OPC …”
Section: Introductionmentioning
confidence: 99%